Network Pharmacology for Identifying Bioactive Compounds in Syzygium cumini with Multi-Targeting Potential for Diabetes and Cardiovascular Disease - Lakshmi Thangavelu; Abin Mahmood Nizar; Sarvesh Sabarathinam; Vinitha Packirisamy (International Journal of Medical Toxicology and Legal Medicine, 2024)
Plant-based medicinal product usage has increased throughout the world for various chronic disorders. Syzygium cumini, a traditional medicinal plant, shows promise in managing diabetes mellitus and cardiovascular disease. This study employs an integrated network pharmacology approach to explore its bioactive compounds' potential. Disease-related genes for diabetes and cardiovascular disease were identified. Functional enrichment analysis and network construction were performed to understand the molecular mechanisms. Six bioactive compounds (Sitosterol, Betulinic acid, crategolic acid, quercitin, kaempferol) were identified, with 211 key target genes associated with diabetes and cardiovascular disease. Crategolic acid, Sitosterol, and kaempferol showed high connectivity. Protein-protein interaction analysis revealed IL6, SRC, ESR, and MAPK3 as key targets. Molecular docking analysis supported potential interactions. It demonstrates the utility of network pharmacology for identifying active compounds and key target genes in traditional medicine. These findings offer insights for drug discovery and further validate the historical use of Syzygium cumini for diabetes-related conditions.